Pendampingan Peningkatan Kualitas Produksi Pastry Pada Siswa-Siswi SMK Kristen Surakarta - Edy, Irwan; Kristian Faskahariyanto; Suryo Adinugroho; Alexander Mario Retto Djong; Truli Nugroho (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Pastry is a type of cake or dough-based food made from flour, fat (such as butter or margarine), water, and sometimes eggs, which generally has a layered and crispy texture. Pastry can be sweet or savory, and is often the base for dishes such as pies, tarts, and other pastries. This community service activity aims to provide training and mentoring to students of Teacher Training Schools (SMK) to be able to produce quality pastries. This community service was carried out at SMK Kristen Margoyudan with the methods used, namely counseling, training and mentoring. The training participants were SMK students with the consideration that SMK students were designed to become workers who were ready to enter the world of work. Training and mentoring were carried out for 1 day, training was carried out by providing training accompanied by direct mentoring by the service team. The results of this service activity were an increase in the level of pastry knowledge, participation level, and activeness of service participants. The achievement indicators were measured by the high level of participation, participant commitment to participate in training and mentoring until completion and the existence of sample pastry products. The result of this activity is reports and articles published in the national community service journal